High-pressure liquid chromatographic method for determination of Sch 29482 in human serum. - Kim, H (1982)
A high-pressure liquid chromatographic method was developed for quantitative determination in human serum of a new penem antibiotic known as Sch 29482 (5R,6S,8R-2-ethylthio-6(1-hydroxyethyl)penem-3-carboxylic acid). The method involves serum extraction at an acid pH with ether, followed by separation on a reverse-phase column and UV light detection at 254 nm. This technique produced a good linear relationship between the peak height ratio and the Sch 29482 concentration, which ranged from 0.09 to 35.64 micrograms/ml. In addition, this procedure proved to be quite specific for Sch 29482, since all beta-lactam antibiotics tested did not interfere with the assay. For high concentrations (greater than 0.5 micrograms/ml), the mean values obtained from the high-pressure liquid chromatographic method correlated very well (r = 0.997) with those obtained from a microbiological assay. This method is accurate and reproducible, with a sensitivity of about 0.09 micrograms per ml of serum. It is useful for monitoring serum drug levels in animals and humans and can also be used for drug pharmacokinetic studies in humans.